As representações sociais dos professores de alunos com síndrome de Down incluídos nas classes comuns do ensino regular. - Castro, Sabrina Fernandes de (2006)
This work has been developed in the graduated curse in Education of the graduated program in Federal University of Santa Maria. This research has the aim of investigating the social rules of teachers that deal with students with Down s syndrome (DS). These students have been enrolled in the first years of elementary education program with the goal to understand how their involvement in class takes place. Although the challenge that this represents the outcomes is very significant since the regular elementary schools can become environments for DS students. Once, just a small fraction of elementary school admits DS students, there is a challenge as well as need of transformation of the system to have this practice wide spread. In this scenario it is imperative to hear teachers to know they think, feel and their ideas that is their social representations. It is known that a social representation has an impact in the daily activities as well as in the decision making and practicing. The representation make possible to draw a relationship between the dynamics that involve the language, thought and action. To carryout this research we have used the methodology of content analyses with allows to have a wide perspective of social representations on the school context. Analyzing the speech of teachers we pursuit the understanding of the representation that they have of the DS students. Where special attention has been spend to the following items:1) the phenotype; 2) the myths; 3)the terminology; 4) the feelings; 5) the attitudes. By analyzing the obtained data it is possible to conclude that the teacher s representations of DS students are separated from the inclusive practice. In addition, it has been verified that is important to have a specific continuing education for the teachers. With the inclusion teachers are learning to see that which student has his own particularities and a history of life and family that is the student is no longer more than one in class. In this way, the study of teacher s social representation of DS students is away to review the differences in the classroom. Leading to reflections and opening doors to new view, new paths in a process of active participations it is worth to mention that the result that we pursue is a comprehension and description of the process and not the definitive truth. Finally, we have highlighted what Moscovici (1978) states; the study is provisory and open and must be argued and studied with depth.